Association between major dietary patterns and obesity phenotypes in southwest China: baseline survey results from Hechuan - Shaomei, Wang; Dezhi, Jing; Mengfen, Li; Huaan, Duan; Xianbin, Ding; Juan, Peng; Xia, Li; Yanfeng, Zhu (Frontiers in Nutrition, 2024)
Background This study aimed to identify the main dietary patterns in Hechuan and clarify how they are associated with obesity phenotypes. Methods A cross-sectional study was conducted based on a baseline survey of a general population cohort study in southwest China. A semi-quantitative food frequency questionnaire (FFQ) was used to investigate the dietary habits of the participants in the past year. Principal component analysis was conducted to identify the main dietary patterns, and multinomial logistic regression analysis was conducted to describe the association between the major dietary patterns and obesity phenotypes. Results Three major dietary patterns were identified. The participants who followed the wheaten food dietary pattern had a higher likelihood of having metabolically normal obesity (MHO) (odds ratio (OR) 1.05, 95% confidence interval (CI) 1.02–1.08), metabolically abnormal normal weight (MUNW) (OR 1.08, 95%CI 1.00–1.16), and metabolically abnormal obesity (MUO) (OR 1.07, 95%CI 1.04–1.11). Specifically, those with the highest wheaten food dietary pattern were 1.60 times more likely to have MHO (OR 1.60, 95%CI 1.25–2.05), 2.62 times more likely to have MUNW (OR 2.62, 95%CI 1.28–5.37), and 2.01 times more likely to have MUO (OR 2.01, 95%CI 1.51–2.69) than those with the lowest wheaten food dietary pattern. Conclusion The wheaten food dietary pattern may increase the risk of obesity and metabolic abnormalities. Therefore, timely interventions should be carried out for this group of people.